Upaya Meningkatkan Kemampuan Berhitung Permulaan Anak Usia 3-4 Tahun Melalui Permainan Kubus Angka - Khasanah, Iis (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This study aims (1) To know the ability to count the beginning of children aged 3-4 years in KB Cheers Nonidah Purwosari Tlogowungu Pati. (2) To find out whether the number cube game can improve the ability of counting children aged 3-4 years. This research was conducted in two stages, namely cycle I and cycle II. In the process, the number cube for improving childrens numeracy is carried out with two cycles, the first cycle is classical, cycle II with the division of 4 groups. The results of the data analysis and observation through the number cube shows an increase from the pre cycle of 29% of children who complete the ability to count, up in the first cycle to 61%. That is, an increase of 32%. And in the second cycle increased to 83.7% and an increase of 83.7%. The results achieved in cycle II already meet the determined completion target, which is 80% of the total children get the value with the category of the total value of 85. The increase of this average value proves the success of number cube game to improve the counting ability of children.